Factors influencing the implementation of 30 minutes structured physical activity in after-school programs - Hastmann, Tanis J. (Kansas State University, 2008)
After-school programs are considered to have great potential to provide opportunities for increasing physical activity. One factor that may influence the success of a physical activity intervention is program implementation. The purpose of this study is to understand factors that influence implementation of a 30 minutes structured physical activity session in an after-school program. After-school staff (organizational leaders, site program managers and fourth grade group leaders), from four after-school sites attended three trainings over the academic year and were given the goal to implement 30 minutes of daily structured after-school physical activity to fourth grade children following CATCH guidelines. At the end of the year two organizational leaders (mean age = 55.0), four program managers (mean age = 27.3), and 13 group leaders (mean age = 21.3) were interviewed (N = 19) and completed a survey. Interviews were recorded, transcribed and analyzed using QSR NVivo software. Several factors influencing implementation were revealed. First, program managers and group leaders believed that they were successful in leading structured physical activity. However, their definition of success was less than the evidence-based protocol that required structured physical activity five days a week for 30 minutes. Staff believed that increasing the amount of unstructured activity offered and offering structured physical activity three days a week met the standard. Second, structured physical activity was not implemented as intended due to several organizational and staff barriers. The organizational barriers included: prioritizing physical activity, lack school administration support, lack program manager support, high group leader turnover, and low training attendance. The staff barriers included: low group leader motivation, and providing children with enjoyable CATCH games. Third, implementation of structured physical activity was facilitated by several organizational and staff variables. These facilitators included equipment/gym space, training, scheduling structured physical activity, support from the organizational leaders, and program manager and group leader self-efficacy. The final factor influencing program implementation was the use of individual strategies by program managers and group leaders. These individual strategies included restructuring the after-school program, obtaining physical education teacher support, and participating with the children in structured physical activity. Findings from this study suggest that the success of the after-school intervention is dependent on many factors, including several organizational system variables, as well as several staff variables. Program managers and group leaders negotiated these organizational and staff barriers and believed that they were successful in leading structured physical activity. However, their definition of success was less than the evidence-based protocol that required structured physical activity five days a week for 30 minutes. They defined successful implementation as increasing the amount of structured and unstructured physical activity daily. Future research should examine if targeting the organizational and staff variables identified in this study leads to greater program implementation.
Keywords: After-school; Physical activity; Qualitative; Implementation; Obesity; Barriers; Health Sciences, Public Health (0573)